Heroic identity and biographical narratives: the memory of sport by olympic athletes - Rubio, Katia (2019)
The Olympic sport, as well as other human phenomena, presents the marks of a complex phenomenon that configures itself as social and perpetuates in the athlete as the narrator of events that contribute to the formation of a sports imaginary. This is because as a protagonist of the show he is both the hero of his time and the anonymous in a future called post-career. Glued to this social role, it distances itself from other identities that make it a citizen or a recognized professional in some work activity away from sport after the competitive phase is over. And in this condition, mobilized by the demands of the sports environment, the athlete is obliged to perform the function determined by the institutions and sponsors, reducing his expressive potential as a person. The objective of this text is to reflect on the trajectory of a research that at first it sought data, and when it came to subjects who were not objects, it became a method. To this end, the text presents the theoretical-epistemological trajectory of a process that goes more than two decades and is alive and changing.